Fair value accounting and financial stability - Andrea Enria; Lorenzo Cappiello; Frank Dierick; Sergio Grittini; Andrew Haralambous; Angela Maddaloni; Philippe Molitor; Fatima Pires; Paolo Poloni (European Central Bank (ECB), 2004)
Accounting standard setters are considering the wider use of fair value accounting. This paper focuses on the financial stability implications of a move in the banking sector from the current accounting framework to full fair value accounting. A simulation exercise is performed on how various external shocks affect the balance sheet of an average European bank under the two frameworks. The paper further investigates the impact of the alternative framework on the main balance sheet items, and the interaction with banks' risk management, supervisory tools and statistical requirements. It also examines how the application of fair value accounting to banks' trading book has impacted their share price volatility. It is concluded that the introduction of full fair value accounting could have a significant effect in terms of income volatility, procyclicality of bank lending and more generally financial stability. Hence, any move towards this alternative accounting framework should be gradual.
Keywords: G14; G21; G28; M41; 330; accounting; banks; fair value; financial regulation; financial reporting; financial stability; risk management.; Bilanzielle Bewertung; IFRS; Finanzsektor; Bank; EU-Staaten